Moderating severe personality disorders : - Millon, Theodore (J. Wiley & Sons, 2007)
Acknowledging the primacy of the whole person, Moderating Severe Personality Disorders: A Personalized Psychotherapy Approach takes into account all of the complexities of human nature - family influences, culture, neurobiological processes, unconscious memories, and so on--illustrating that no part of human nature should lie outside the scope of a clinician's regard.